Influence of Internal Structure on Breaking Process of Short-Lived Landslide Dams - Meng, Chu-Ke; Chen, Kun-Ting; Niu, Zhi-Pan; Di, Bao-Feng; Ye, Yu-Jian (Frontiers in Earth Science, 2021)
The diversity of the landslide dam structure will result in the difference in the dam body’s seepage. In this paper, based on two kinds of soil bodies of different particle gradations, fourteen groups of structures of the landslide dam are designed to generalize different seepage developments and breaking processes. The study shows that the saturation and seepage evolution characteristics of the landslide dam's seepage have a considerable influence on the landslide dam’s breaking characteristics. An empirical formula is fitted according to the time-seepage degree curve of the landslide dams of different breaking processes to predict the breaking forms of the landslide dams before the dam break. During the water storage process of the landslide dam, the seepage's saturation process inside the dam body reduces the stability of the landslide dam, thus affecting the evolution of the failure process after it has started. In the experiment, it is found that the growth rate of the seepage degree of the landslide dam is inversely proportional to the growth rate of the dam breach area. Although the internal penetration of landslide dams is usually undervalued, the result verifies that the study on the seepage process before the breaking of landslide dam is conductive for further understanding the breaking mechanism of the landslide dam.